ЖАМОАНИ БОШҚАРИШ: РАҲБАРНИНГ УМУМИЙ ФУНКЦИОНАЛ ВА БОШҚАРУВ КЎНИКМАЛАРИ (ижтимоий психологик аспект) - Еримбетов, Б.; Махмудов, А. (SCIENCE and SOCIETY, 2017)
The article deals with the general functional and managerial leadership skills, management, their role in the practice of management. There are given the definitions of the concepts of "staff management", "management", the author briefly describes their differences. It denotes the relevance of the study of the problem of forming the common functional and managerial skills of young leaders. The article has scientific and educational value for students, aspirants seekers, managers, administrative workers, specialists in human resource management.
Keywords: head; manager; staff; to organize the control; management; leadership; common functional and managerial skills